KAJIAN STRUKTURALISME PADA PUISI "SAJAK" KARYA SUBAGIO SASTROWARDOYO - Hermawan, Dimas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Poetry is a literary work that expresses the author"™s thoughts and feelings imaginatively through the effective use of language, focusing on the careful arrangement of it"™s structural components to create the impression desired by the author. However sometimes a poetry is too difficult to understand, causing many people to feel less interested and motivated to read poetry. In the field of literature, the study of poetry becomes an important activity in an effort to uncover and understand the hidden meanings that the author wishes to convey in their poetry. At present, there are various approaches that can be used to study poetry, one of which is the structuralism approach. This study to examine in an effort to uncover and understand the hidden meanings that Subagio Sastrowardoyo wants to convey in his poetry titled "Sajak". This study uses a qualitative method with a hermeneutic approach. In the meantime, the data collection technique using documentation with data analysis techniques using deconstruction. Based on the results of the structuralism study, the poetry "Sajak" by Subagio Sastrowardoyo tells the story of an inner struggle due to facing various life problems that cause suffering. Various problems made author"™s life feel increasingly bound and trapped in misery, to the point where he even contemplated suicide. Furthermore, this study hopes to provide additional references and relevance to the study of literature in Indonesia, particularly in the study of poetry.